NORT: Runtime Anomaly-based Monitoring of Malicious Behavior for Windows - MILEA, Narcisa Andrea (Institutional Knowledge at Singapore Management University, 2011)
Protecting running programs from exploits has been the focus of many host-based intrusion detection systems. To this end various formal methods have been developed that either require manual construction of attack signatures or modelling of normal program behavior to detect exploits. In terms of the ability to discover new attacks before the infection spreads, the former approach has been found to be lacking in flexibility. Consequently, in this paper, we present an anomaly monitoring system, NORT, that verifies on-the-fly whether running programs comply to their expected normal behavior. The model of normal behavior is based on a rich set of discriminators such as minimal infrequent and maximal frequent iterative patterns of system calls, and relative entropy between distributions of system calls. Experiments run on malware samples have shown that our approach is able to effectively detect a broad range of attacks with very low overheads.